2007
DOI: 10.1111/j.1365-2109.2007.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and fatty acids in wild and pond-reared mud crab Scylla serrata (Forsskål) during ovarian maturation and spawning

Abstract: Wild‐caught and pond‐reared female mud crab Scylla serrata at different stages of ovarian maturation were collected from Samar and Capiz, Philippines. Crabs were categorized into five stages according to the external morphological and microscopic appearance of the most advanced oocytes. The ovaries, hepatopancreas, muscle and newly spawned eggs (NSE) were analysed for lipid class components and fatty acids. Total lipid was higher in pond‐reared than in wild‐caught crabs but increased with ovarian maturation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 34 publications
4
38
0
Order By: Relevance
“…As a corollary to the external and histological classification, the biochemical profiles of the same batch of ovaries were determined separately (Alava, Quinitio, de Pedro, Priolo, Orozco & Wille 2007). The characteristics of the quality and quantity of egg yolk proteins incorporated into the eggs may have a direct and measurable effect on larval survival.…”
Section: Discussionmentioning
confidence: 99%
“…As a corollary to the external and histological classification, the biochemical profiles of the same batch of ovaries were determined separately (Alava, Quinitio, de Pedro, Priolo, Orozco & Wille 2007). The characteristics of the quality and quantity of egg yolk proteins incorporated into the eggs may have a direct and measurable effect on larval survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that optimizing feed formulation specifically for broodstock should enhance egg quality, gonad maturation, and fecundity in crustaceans (Rodríguez‐González et al 2009), and therefore reflect their nutrient requirements and metabolic needs (Alava et al 2007). Prior experiments conducted on red claw in our laboratory indicated that dietary EPA and DHA were inefficiently utilized during vitellogenesis, suggesting that a costly diet with high PUFA content may not meet nutritional demands.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are one of the main sources of metabolic energy and have important functions as cytoplasm and membrane constituents of cells affecting structural and physiological properties. Wild and pond‐sourced crab S. serrata during ovarian maturation and spawning indicated that the ovaries and newly spawned eggs contain high levels of highly unsaturated fatty acids (HUFA) such as arachidonic acid (ArA, 20:4n‐6), eicosapentaenoic acid (EPA, 20:5n‐3) and docosahexaenoic acid (DHA, 22:6n‐3) (Alava, Quinitio, de Pedro, Orosco, Priolo & Wille 2007). Moreover, phospholipids particularly phosphatidyl choline (PC) were also accumulated in large amounts in ovaries and newly spawned eggs.…”
Section: Introductionmentioning
confidence: 99%